Mina's matchbox - Ogawa, Yōko, 1962- (Pantheon Books, 2024)
"In the spring of 1972, twelve-year-old Tomoko leaves her mother behind in Tokyo and boards a train alone for Ashiya, a coastal town in Japan, to stay with her aunt's family. Tomoko's aunt is an enigma and an outlier in her working-class family, and her magnificent home-and handsome, foreign husband, the president of a soft drink company-are symbols of that status. The seventeen rooms are filled with German-made furnishings; there are sprawling gardens and even an old zoo where the family's pygmy hippopotamus resides. The family is just as beguiling as their mansion-Tomoko's dignified and devoted aunt, her German grandmother, and her dashing, charming uncle who confidently sits as the family's patriarch. At the center of the family is Tomoko's cousin Mina, a precocious, asthmatic girl of thirteen who draws Tomoko into an intoxicating world full of secret crushes and elaborate storytelling. In this elegant jewel box of a book, Yoko Ogawa invites us to witness a powerful and formative interlude in Tomoko's life, which she looks back on briefly from adulthood at the novel's end.? Behind the family's sophistication are complications that Tomoko struggles to understand-her uncle's mysterious absences, her German grandmother's experience of WWII, and her aunt's misery. Rich with the magic and mystery of youthful experience, Mina's Matchbox is an evocative snapshot of a moment frozen in time-and a striking depiction of a family on the edge of collapse"--